Phenotypic Characterisation of Selected Cultivars of Manihot esculenta Crantz (Cassava) - Otebe, J.A.; Jayeola , A.A.; Olawuyi , O.J. (International Journal of Scientific Research in Biological Sciences, 2024)
Various accessions of Manihot esculenta Crantz (cassava) exhibit notable morphological similarities in their stems, leaves, and root systems. The genetic enhancement of cassava relies heavily on the crop`s diversity and variability. This study focused on the characterisation of eleven cassava cultivars through morphological methods. The experiment, structured in a complete randomised design each with three replicates, underwent detailed statistical analysis using SAS version 2010. Analysis of variance (ANOVA) showed significant differences in the performance of the cultivars across all traits at p ? 0.05. Among the cultivars, Agric (White), Nwator, Allimeme (Brown), and Vitamin A (Brown) demonstrated superior growth characteristics. The trait with the highest heritability was the number of branches per plant, with an estimate of 99.79%, while the number of leaf lobes per plant showed the lowest heritability at 95.04%. At 327.37 and 327.71, respectively, the highest values of the Phenotypic Coefficient of Variation (PCV) and Genotypic Coefficient of Variation (GCV) were found for the number of branches per plant. Conversely, the number of leaf lobes per plant accounted for the lowest GCV (9.24) and PCV (9.48). The most significant genetic advance was noted in the number of branches per plant (674.68), whereas the least was in the number of leaf lobes per plant (18.58). Plant height displayed a strong positive correlation with leaf area (r = 0.69) and a moderate positive correlation with stem girth (r = 0.51). Principal Component Analysis (PCA) indicated that Prin. 1 accounted for the largest proportion of variance, contributing 32.02% with an eigenvalue of 7.36. Consequently, Agric (White), Nwator, Allimeme (Brown), and Vitamin A (Brown) are promising cassava cultivars that merit documentation, hybridisation and conservation for the improvement of cassava germplasm.